A novel bio- inspired algorithm for hunting in multi robot scenario - Poorva Agrawal; Himanshu Agrawal; Vidyasagar Potdar (Institute of Advanced Engineering and Science, 2019)
In a multi-robot scenario, cooperative hunting is a key issue when a group of robots are hunting for evader/evaders and when the location of the evader is continuously changing. Cooperative hunting is addressed in this paper by proposing a novel bio inspired Corner Dragging Algorithm (CDA). Corner Dragging Algorithm operates by making an alliance of robots that drag the evader towards any one of the four corners; whichever is closest to the evader. Different shapes of obstacles are avoided during this pursuit. While developing the Corner Dragging Algorithm, we analyze the shortcomings and advantages of some of the existing algorithms including dynamic alliance and formation construction algorithm and incorporate these changes in our design to achieve improved results. Performance of the algorithm is evaluated on the basis of simulation in MATLAB.